Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/curroncol29100580
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and Radiotherapy as an Antitumoral Long-Range Weapon—A Partnership with Unsolved Challenges: Dose, Fractionation, Volumes, Therapeutic Sequence

Abstract: Immunotherapy, the modern oncological treatment with immune checkpoint inhibitors (ICIs), has been part of the clinical practice for malignant melanoma for more than a decade. Anti-cytotoxic T-lymphocyte antigen 4 (CTLA4), anti-programmed cell death Protein 1 (PD-1), or anti programmed death-ligand 1 (PD-L1) agents are currently part of the therapeutic arsenal of metastatic or relapsed disease in numerous cancers; more recently, they have also been evaluated and validated as consolidation therapy in the advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Eligibility criteria, particularly relevant in neuro-oncology, and inadequate phase II study designs have been critically reviewed elsewhere ( 239 ). As for the design of clinical trials for glioblastoma to improve the effectiveness of immunotherapy/oncolytic virotherapy in general, the following aspects, supported by clinical data, must be taken into account ( 196 , 197 , 240 , 241 ). First, the circulating blood within the blood vessels is recognized as an organ at risk for radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eligibility criteria, particularly relevant in neuro-oncology, and inadequate phase II study designs have been critically reviewed elsewhere ( 239 ). As for the design of clinical trials for glioblastoma to improve the effectiveness of immunotherapy/oncolytic virotherapy in general, the following aspects, supported by clinical data, must be taken into account ( 196 , 197 , 240 , 241 ). First, the circulating blood within the blood vessels is recognized as an organ at risk for radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported an association between the radiotherapy dose/volume and lymphopenia in glioblastoma ( 56 , 77 , 192 , 193 ). The severity of radiation-induced lymphopenia depends on the technique of radiotherapy, fraction number (fractionation regimen), dose per fraction (irradiation dosage), field size, and other variables ( 78 , 194 197 ).…”
Section: Implications Of Standard Therapy-related Immunosuppression F...mentioning
confidence: 99%
“…The radiation dose, fractionation schedule, and radiation volume should be carefully formulated according to the individual context of each patient to avoid severe lymphopenia. To mitigate radiation-induced lymphopenia, hypofractionated radiation, reduction of the traditional clinical target volume, sparing healthy regional lymph nodes, where the T cell priming and activation takes place, and large blood vessels are worth exploring in the modern era of immunotherapy and technological improvements in targeting and delivery of RT [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression induced via concurrent radiochemotherapy–immunotherapy, as well as the immunosuppression associated with elective irradiation of lymph nodes, could be the cause of failures reported in clinical trials such as JAVELIN Head and Neck 100 (NCT02952586). Even if it refers to Pembrolizumab, an ICI agent other than Nivolumab, a sequential combination is considered optimal in the case of delivering radio-chemotherapy and immunotherapy [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%